Hipersuperficies generalizadas en Cn - Fernandez Sánchez, Percy (2013)
The main aim of this paper is proof that the reduction of the singularities of a generalized hypersurfaces agrees with a reduction of singularities of its separatrix; which is a generalization of the result presented in [8] by the first two authors.